Electrically-controlled suppression of Rayleigh backscattering in an integrated photonic circuit - Örsel Oğulcan E.; Noh Jiho; Bahl Gaurav (Nanophotonics)
Undesirable light scattering is a fundamental cause for photon loss in nanophotonics. Rayleigh backscattering can be particularly difficult to avoid in wave-guiding systems and arises from both material defects and geometric defects at the subwavelength scale. It has recently been shown that systems exhibiting chiral dispersion due to broken time-reversal symmetry (TRS) can naturally mitigate Rayleigh backscattering, yet this has never been explored in integrated photonics. Here we demonstrate the dynamic suppression of disorder-induced Rayleigh backscattering in integrated photonics even when defects are clearly present. Our experiments are performed using lithium niobate on insulator resonators in which TRS is broken through an electrically-driven acousto-optic interaction. We experimentally observe near-complete suppression of Rayleigh backscattering within the resonator by measuring the optical states and through direct measurements of the back-scattered light. We additionally provide a new and intuitive generalization argument that explains this suppression of backscattering as a form of topological protection in synthetic space.